Pengaruh Pelatihan dan Disiplin Kerja terhadap Kinerja Pegawai - Solin, Nurcahaya Benediate; Hermana, Cecep (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to assess the effect of training and work discipline on employee performance. The method used is a literature review using a quantitative approach, collecting and analyzing data from various scientific articles and recent publications in the last five years. The results showed that training plays a role in improving employee’ knowledge, skills and work attitudes. Meanwhile, work discipline ensures the application of the these abilities consistently and responsibly. Training and work discipline simultaneously have a positive and significant effect on employee performance. Keywords: Discipline, Employee Performance, Training, Work